2020
DOI: 10.21203/rs.3.rs-100929/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rosmarinic Acid Induces Proliferation Suppression of Hepatoma Cells Associated with NF-κB Signaling Pathway

Abstract: Background: Rosmarinic acid (RA) is a natural phenolic compound that acts as a Fyn inhibitor by 53 homology modeling of the human Fyn structure. Therefore, the apoptosis mechanism related to NF-κB signaling pathway induced by RA in HepG2 was investigated. Methods: The cell growth, apoptosis, and proliferation of HepG2 regulated by various concentrations of RA were studied. The proteins expression of MMP-2, MMP-9, PI3K, AKT, NF-κB, and apoptosis-related proteins Bax, Bcl-2, cleaved caspase-3 were detected. Resu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Other reports showed that the perilla extract rich in RA [74] and RA compounds had a considerable inhibitory effect on inflammation via suppression of the NF-κB signaling pathway during both in vitro and in vivo experiments [103,104]. Moreover, RA inhibited the invasion and migration of human glioma cells [85] and human hepatoma cells through the PI3K/Akt/NF-κB signaling pathway [105].…”
Section: Discussionmentioning
confidence: 93%
“…Other reports showed that the perilla extract rich in RA [74] and RA compounds had a considerable inhibitory effect on inflammation via suppression of the NF-κB signaling pathway during both in vitro and in vivo experiments [103,104]. Moreover, RA inhibited the invasion and migration of human glioma cells [85] and human hepatoma cells through the PI3K/Akt/NF-κB signaling pathway [105].…”
Section: Discussionmentioning
confidence: 93%